If 5-4=23, 6-16=32, 9-9=78, 3-9=6 then 3-61=??

5 - 4 = 23 (5^2 - sqrt(4)) 6 - 16 = 32 (6^2 - sqrt(16)) 9 - 9 = 78 (9^2 - sqrt(9)) 3 - 9 = 6 (3^2 - sqrt(9)) 3 - 61 = 1.********** (3^2 - sqrt(61))

Answer is 1.19 Method is sq(first no.) - sqrt(second no.) = ans 5-4 = 5^2 - sqrt(4) = 25-2 = 23 6-16 = 6^2 - sqrt(16) = 36-4 = 32 9-9 = 9^2 - sqrt(9) = 81-3 = 78 3-9 = 3^2 - sqrt(9) = 9-3 = 6 3-61 = 3^2 - sqrt(61) = 9-7.81 = 1.19

If 5 - 4 = 23 8 - 1 = 63 6 -16 = 32 9 - 9 = 78 3 - 9 = 6 then 3 - 81 = ?

IF

5 - 4 = 23 8 - 1 = 63 6 - 16 = 32 9 - 9 = 78 3 - 9 = 6

Then

3 - 81 = ?

3 2 = 7 5 4 = 23 9 9 = 78

3 81 = ??